Data supporting: One-dimensional approximation of heat transfer in flashlamp-assisted automated tape placement - Danezis, Anastasios; Skordos, Alexandros A.; Williams, David (Cranfield University, 2023)
Comparison 1D_2D: predictions of 1D and 2D methodologies for a wide range of processing rates, deposited material thickness and pulsing conditions. Data of computational effort for equivalent predictions are also included.
Keywords: 'Process modelling'; 'Finite element analysis'; 'Tape placement'; 'Heat transfer modelling'; 'Automated Tape Placement (LATP)'